Coastal dunes of Ontario: distribution and geomorphology - Martini, Peter (Géographie physique et Quaternaire, 1981)
Transverse dunes (fore-dunes), parabolic dunes, rare cliff-top dunes, and blowouts are found in Ontario. Many of these coastal dunes are land-locked on abandoned sand plains of partially drained early-post glacial lakes and seas. Others are part of coastal systems found at different stages of evolution along the Great Lakes. An idealized coastal system, as is for great part well developed at Wasaga Beach, includes the following elements: a few metres high foredunes partially deflated and breached by wave washover; low, long, narrow, marshy zones landward from the foredunes: the "pannes"; a wide sequence of numerous beach ridges capped by small (2 m high) stabilized foredunes, and separated by long shallow swales covered by water for several months of the year; intensely deflated transverse dunes which record raised coastlines of old lakes; and finally, high (up to 25 m) nested parabolic dunes showing progressive landward increase in height. These high dunes have developed over sandy, gravelly bars of early Holocene lakes, and have prograded for a short distance over lagoons. Most of the dune systems found along the Great Lakes have developed in the last 3-5000 years. Some of them have been intensely affected by man during the last two centuries, particularly by logging, agriculture, and recreational activities. Some dune fields have been completely flattened, others on the contrary have been reactivated by deforestation, and new dunes have formed and have migrated landward onto forests and cultivated fields.